Microbiological Analysis of Antioxidant and Iron-Based Prebiotic Milk Cake - Moumita Das; Rita Mondal; Pragya Tiwari; Ranajit Kumar Khalua (The Bioscan, 2024)
This study investigates the microbiological safety and functional attributes of antioxidant and iron-enriched prebiotic milk cakes formulated using buffalo milk, kiwi fruit powder, and dates powder. Four treatment combinations (T0, T1, T2, and T3) were prepared, varying the proportions of these functional ingredients. Microbiological analyses, including total plate count (TPC), yeast and mold count, and coliform detection, were conducted to ensure product safety. The results showed TPC values ranging from 1.2 × 10² to 1.5 × 10² CFU/g, yeast and mold counts from 0.5 × 10² to 0.8 × 10² CFU/g, and the absence of coliforms in all samples. T1 exhibited the highest antioxidant activity and iron content due to its optimal levels of kiwi fruit and dates powders. This research demonstrates the potential of functional milk cakes as a safe, nutritious, and innovative food product enriched with prebiotics and antioxidants.